PENGARUH GAYA MENGAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR LAY UP SHOOT - Gilang Ramadan; Dedi Iskandar (IKIP PGRI Bojonegoro, 2018)
Abstract: The aim of this study was to determine the effect of Reciprocal teaching styles and teaching styles Exercise as well as learning motivation towards learning outcomes Lay UpShoot.The research was conducted on students and SMA Negeri 1 Cigugur. This study uses a treatment by the level of 2 x 2. The sample consisted of 28 students as well as students. The data analysis technique is a two-track analysis of variance (ANOVA) and then followed by Tukey's test at a significance level Î± = 0, 05. The results of this study indicate that (1). Value of learning outcomes Lay Up Shoot in the treatment higher Reciprocal teaching style with the results of 50% (14) above the average of the value style of teaching exercises that only 39.29% (11) above average in SMA 1 Cigugur. (2). Value learning outcomes Lay Up Shoot in the treatment of Reciprocal teaching style of learning motivation high (A1B1)is higher than the value of teaching style Exercise high learning motivation (A2B1)in SMA Negeri 1 Cigugur. (3). Value learning outcomes Lay Up Shoot in the treatment of Reciprocal teaching style low learning motivation (A1B2)is lower than the value of teaching style Exercise low learning motivation (A2B2)in SMA Negeri 1 Cigugur.Keyword:Â Reciprocal teaching styles, teaching styles Exercise, learning motivationAbstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dari gaya mengajar Resiprokal dan gaya mengajar Latihan serta motivasi belajar terhadap hasil belajar Lay Up Shoot. Penelitian ini dilakukan pada siswa maupun siswi SMA Negeri 1 Cigugur. Penelitian ini menggunakan treatment by level 2 x 2. Sampel terdiri dari 28 siswa maupun siswi. Teknik analisis data adalah analisis varians dua jalur (ANAVA) dan selanjutnya dilanjutkan dengan uji Tukey pada tingkat signifikansi Î± = 0, 05. Hasil penelitian ini menunjukkan bahwa (1). Nilai hasil belajar Lay Up Shoot pada perlakuan gaya mengajar Resiprokal lebih tinggi dengan hasil 50% (14 orang) di atas rata-rata dari nilai gaya mengajar Latihan yang hanya 39,29% (11 orang) di atas rata-rata di SMA Negeri 1 Cigugur. (2). Nilai hasil belajar Lay Up Shoot pada perlakuan gaya mengajar Resiprokal motivasi belajar tinggi (A1B1) lebih tinggi dari nilai gaya mengajar Latihan motivasi belajar tinggi (A2B1) di SMA Negeri 1 Cigugur. (3). Nilai hasil belajar Lay Up Shoot pada perlakuan gaya mengajar Resiprokal motivasi belajar rendah (A1B2) lebih rendah dari nilai gaya mengajar Latihan motivasi belajar rendah (A2B2) di SMA Negeri 1 Cigugur.Kata kunci:Â Gaya Mengajar Resiprokal, Gaya Mengajar Latihan, motivasi belajar